Planning foundations and programs - a critical study - جديد, خلود; وليد صيداوي , (Latakia University Journal -Engineering Sciences Series, 2024)
Planning foundations and programs represent the urban foundation upon which organizational plans in cities are built. They are guiding standards that must be adhered to and developed in a way that is compatible with spatial structures. Their results are measured and evaluated on a regular basis, to identify deficiencies within them and address and update them, for the purpose of achieving their goal of building a planning output that meets the requirements. Rapid urban growth. Upon careful and analytical review of many organizational plans in Syrian cities (the Tartous city plan, for example), in the various stages of its development, we found that it was drawn up according to the foundations and planning programs that were formulated for the first time in the year 1970, and which turned into rigid templates, which left the inability of the planning programs and systems. Building, its planning output was the same depending on the different spatial and temporal structures, despite the great social, economic and political variables. To address this problem with the burdens it placed on rapid, uncontrolled growth, and the uncontrollable adverse consequences it left behind (low standard of living - weak investment opportunities - poor health services - increased rate of violations on the regulatory plan - expansion at the expense of agricultural lands - deficit in... Public transportation system - population overcrowding...), it was necessary to conduct a critical analytical study of the planning mechanisms (planning foundations and programs) on which the organizational plans in Syrian cities are built, relying on a theoretical base of the basic concepts of urban planning at the global level, with analysis The precise planning mechanisms in the city of Seoul, as the fastest urban development, has historically moved from the foundations and programs of traditional urban planning to urban renewal in a sustainable manner, to achieve the goal of the research by the necessity of working on issuing foundations and planning programs that change with the change in time and place, taking into account spatial specificity and the temporal scope.